The Importance of Religious Literacy in Critical Thinking and Creativity in Junior High School Students - Putri, Annisa Ningtias Cevie; Syafe'i, Makhmud; Firmansyah, Mokh. Iman (International Journal of Multidisciplinary Research of Higher Education, 2024)
This study aims to analyze the impact of the School Literacy Movement program on improving students' religious literacy and critical thinking skills in schools. The scope of this study includes the implementation of School Literacy Movement which integrates religious reading, the habit of reading for 30 minutes, as well as joint reading activities held twice a month (read a thon). The method used in this research is a quantitative approach with an experimental collecting data through observation and interviews with students and teachers involved in the program. The results showed that the School Literacy Movement program plays an important role in improving students' understanding of religious values as well as honing their critical thinking skills. Reading habits and Read a thon activities also increased students' interest in reading, strengthened social relationships and enriched their insights in a religious context. This study concludes that a literacy program that integrates religious materials and reading and writing habits can have a positive impact on students' intellectual and moral development. This program can be a useful model to be implemented in other schools to improve the quality of religious literacy in Indonesia.